Motto in the creation of Russian Romanticicsm. Sources and functions - Sadzińska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article is an attempt at a comprehensive analysis of the typological suitability of the mottos in Russian Romanticism, their sources and trends in Russian Romanticism: the Decembrists, the Lyubomudry Society and Pushkin with the poets and writers from his circle.